USING KAHOOT, CANVA, AND MENTIMETER IN TEACHING ENGLISH: EFFECTIVENESS, ENGAGEMENT, AND DIGITAL PEDAGOGY - Khushbokova Gulshoda (Western European Studies, 2025)
This study examines the effectiveness of Kahoot, Canva, and Mentimeter as digital tools for enhancing English language teaching and learning. It focuses on how these platforms support learner engagement, vocabulary development, formative assessment, and collaborative learning in EFL classrooms. By integrating interactive quizzes, visual materials, and real-time polling, teachers can create learner-centered lessons that improve motivation and communication skills. The analysis highlights how each tool contributes to active learning and how technology-mediated tasks promote meaningful participation. The findings emphasize that the use of Kahoot, Canva, and Mentimeter aligns with 21st-century pedagogy and supports the development of digital literacy in English language learners.
Keywords: Kahoot; Canva; Mentimeter; English language teaching